Experimental trials to detect the lateral displacement on granular material embankment inserted geosynthetics due to the vertical loads - Widodo, Selamet (Jurnal Inovasi Teknologi, 2024)
The usage of geosynthetics to improve the bearing capacity on granular material of embankment construction is worldwide familiar applied. The paper elaborates the lateral displacement of embankment inserted geosynthetics resulted vertical load on the top of embankment. This type of construction is applied like Mechanically Stabilized Earth- Retaining Wall (MSE-RW). Varied distances of inserted geosynthetics with low tensile strength on granular material of embankment for 20, 30, 40, 60 respectively cm installed on totally 140 cm-high of embankment. Each of layer is installed with varied distances with 120 cm -wide must be wrapped in order to avoid loses grains of granular material of embankment. The varied vertical surcharge at the above of embankment started with 19, 34, 49 kg respectively. The result of research indicates that number layer with inserted geosynthetics on granular material of embankment influences the lateral deflections which much more layers of geosynthetics or smaller vertical distance of geosynthetics provides smaller lateral deflection.  Beside that increased vertical load implies the lateral deflection is increased.